2020
DOI: 10.1371/journal.pone.0231091
|View full text |Cite
|
Sign up to set email alerts
|

Acute high temperature exposure impairs hypoxia tolerance in an intertidal fish

Abstract: Acute heat shock has previously been shown to improve subsequent low O 2 (hypoxia) tolerance in an intertidal fish species, a process known as cross-tolerance, but it is not known whether this is a widespread phenomenon. This study examined whether a rock pool specialist, the triplefin fish Bellapiscis medius, exhibits heat shock induced cross-tolerance to hypoxia, i.e., longer time to loss of equilibrium (LOE) and lower critical O 2 saturation (S crit) after recovering from an acute heat challenge. Non-heat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…This is not to say that thermal compensation of ṀO 2,routine and P crit is unimportant for safeguarding hypoxia tolerance with chronic warming, only that the lack of a direct association between P crit and P LOE across treatment groups demonstrates that other factors make an equal or more important contribution to hypoxia tolerance. This disconnect between P crit and absolute hypoxia tolerance as measured by LOE is not unique to the current study, as this has been reported in several other fish species (Borowiec et al, 2020;Mandic et al, 2013;McArley et al, 2020;Speers-Roesch et al, 2013).This points to the fact that the ability to maintain aerobic ATP production at low Pw O2 as measured by P crit , while undoubtedly important, is only one part of a species' total hypoxia tolerance strategy, and that P crit does not necessarily reflect absolute hypoxia tolerance (Mandic et al, 2013;Wood, 2018). In regards to the current study, the mechanisms by which perch are able to improve P LOE with chronic warming despite a higher P crit remain to be elucidated.…”
Section: Cardiorespiratory Thermal Compensation In Normoxia Is Associated With Improved Maintenance Of Aerobic Metabolism In Moderate Hypsupporting
confidence: 64%
“…This is not to say that thermal compensation of ṀO 2,routine and P crit is unimportant for safeguarding hypoxia tolerance with chronic warming, only that the lack of a direct association between P crit and P LOE across treatment groups demonstrates that other factors make an equal or more important contribution to hypoxia tolerance. This disconnect between P crit and absolute hypoxia tolerance as measured by LOE is not unique to the current study, as this has been reported in several other fish species (Borowiec et al, 2020;Mandic et al, 2013;McArley et al, 2020;Speers-Roesch et al, 2013).This points to the fact that the ability to maintain aerobic ATP production at low Pw O2 as measured by P crit , while undoubtedly important, is only one part of a species' total hypoxia tolerance strategy, and that P crit does not necessarily reflect absolute hypoxia tolerance (Mandic et al, 2013;Wood, 2018). In regards to the current study, the mechanisms by which perch are able to improve P LOE with chronic warming despite a higher P crit remain to be elucidated.…”
Section: Cardiorespiratory Thermal Compensation In Normoxia Is Associated With Improved Maintenance Of Aerobic Metabolism In Moderate Hypsupporting
confidence: 64%
“…For example, Todgham et al (2005 ) found that prior exposure to heat shock improved hypoxia tolerance in fish. However, McArley et al (2020) found opposite results, with a longer heat-shock impairing subsequent hypoxia tolerance. Similarly, it has been suggested that the interaction between temperature and hypoxia can impair tolerance ( McBryan et al , 2013 ).…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, it is becoming increasingly common to measure multiple traits in individual fish to obtain a multifaceted view of the responses of organisms to the environment ( Åsheim et al , 2020 ; Gunderson, Armstrong, & Stillman, 2016 ; Joyce & Perry, 2020 ; Nudds, Ozolina, Fenkes, Wearing, & Shiels, 2020 ). However, measuring multiple traits in single individuals results in logistical challenges as prior exposure to a stressful environment has the potential to alter subsequent tolerance, either reducing tolerance due to accumulation of cellular or organismal damage or improving tolerance through phenomena such as heat-hardening and cross-tolerance ( McArley, Hickey, & Herbert, 2020 ; McBryan, Anttila, Healy, & Schulte, 2013 ; Morgan et al , 2018 ; Todgham et al , 2005 ). For example, Todgham et al (2005 ) found that prior exposure to heat shock improved hypoxia tolerance in fish.…”
Section: Discussionmentioning
confidence: 99%
“…The inhalation of hot summer air raises the airway temperature and oxygenation will decrease tending to hypoxemia, with an effect similar to lower ventilation. It is known that summer heat waves may lead to hypoxia, as it has been observed in human communities, animals and marine environments [Frölicher and Laufkötter, 2018;Stillman, 2019;McArley et al, 2020]. It is also known that cardiovascular affections dramatically increase in hot days [Petralli et al, 2012;Grasso et al, 2017] and in urban heat islands [Paravantis et al, 2017] for the effort of combining thermoregulation with intense heart activity needed to compensate for the lower oxygen concentration.…”
Section: Consequences Of the Different Saturation Levels Reached By Oxygen In Bloodmentioning
confidence: 99%